A Rare Case Study of Torsion of a Non-Gravid Uterus - Basnet, Tulasa; Panta, Padam Raj; Sharma, Jyoti; Pokhrel, Amrit (Birat Journal of Health Sciences, 2018)
Torsion of a non gravid uterus is a rare but potentially fatal event. It may lead to rapid clinical deterioration causing irreversible ischemic damage to the uterus. The rarity of the condition and its non specific clinical presentation make the clinical diagnosis difficult. In this report we discuss a case of uterine torsion in a 55 year old postmenopausal lady who presented in emergency with acute abdomen. On examination a huge abdominal mass arising from pelvis was noted. The operative finding was huge fundal myoma with uterine torsion. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 309-311